Rasionalitas Teologi Mu'tazilah - Muhyidin Muhyidin; Nashihin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2021)
Islam in the early days has given rise to various schools of theology. One of the streams that is so famous is Mu'tazilah. Mu'tazilah is a theological school in Islam which is known to be very rational. As a term, the word Mu'tazilah actually existed long before the incident Was}il bin At}a’ separated himself from the Hasan AI-Basri assembly. Namely, when there was a political conflict in the late days of Uthman bin ‘Affan 's leadership, then continued during the time of Caliph ‘Ali bin Abi Talib, there were some of the companions of the Prophet Muhammad who did not want to interfere in these political matters. They isolate themselves (i'tizal), which is then called Mu'tazilah (mu'taziliyyin). Meanwhile, Mu'tazilah as a theological school is attributed to Wasil bin Ata’, who is considered to be the founder. Mu'tazilah formulated the five most fundamental principles, known as al-Usul al-Khamsah (five bases): al-Tauhid, al-‘Adl, al-Wa’du wa al-Wa’id, al-Manzilah bin al-Manzilatain,, and al-Amr bi al-Ma’ruf.. The five bases are arranged systematically and are rationally interrelated.